2021
DOI: 10.1186/s12967-020-02644-x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of the prognostic significance of microRNAs related to metastatic and EMT process among prostate cancer patients

Abstract: The ability of tumor cells to spread from their origin place and form secondary tumor foci is determined by the epithelial–mesenchymal transition process. In epithelial tumors such as prostate cancer (PCa), the loss of intercellular interactions can be observed as a change in expression of polarity proteins. Epithelial cells acquire ability to migrate, what leads to the formation of distal metastases. In recent years, the interest in miRNA molecules as potential future treatment options has increased. In tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 171 publications
(144 reference statements)
0
13
0
Order By: Relevance
“…It is worth remembering however that miRNAs often work synergistically as a regulatory network for gene expression, so the involvement of miR-21 with other miRNAs should be considered. For instance, while this paper was being prepared, another systematic review and meta-analysis was published which reported the prognostic significance of 15 microRNAs related to metastasis and EMT process in PCa patients [ 105 ]. Surprisingly, miR-21 was not included among them, but the authors did acknowledge the link between their selected miRNAs and miR-21 in their discussion, and they concluded that a miRNA panel of biomarkers would be optimal to determine progression risk.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth remembering however that miRNAs often work synergistically as a regulatory network for gene expression, so the involvement of miR-21 with other miRNAs should be considered. For instance, while this paper was being prepared, another systematic review and meta-analysis was published which reported the prognostic significance of 15 microRNAs related to metastasis and EMT process in PCa patients [ 105 ]. Surprisingly, miR-21 was not included among them, but the authors did acknowledge the link between their selected miRNAs and miR-21 in their discussion, and they concluded that a miRNA panel of biomarkers would be optimal to determine progression risk.…”
Section: Discussionmentioning
confidence: 99%
“…The miRNA-34 family comprises miR-34a, miR-34b, and miR-34c. miR-34a is located on chromosome 1p36, whereas, in the human genome, miR-34b and miR-34c are located on chromosome 11q23, clustered as homologous genes that share a common primary transcript [54]. The miR-34 family members are regarded as tumor-suppressive miRNAs due to their synergistic effect with the tumor suppressor p53, as well as their involvement in EMT via EMT-TFs.…”
Section: Mir-34mentioning
confidence: 99%
“…miR-34a inhibits metastasis by directly repressing CD44 [87], a cancer stem cell marker that has been considered to indicate a more mesenchymal phenotype of human PCa cells [88]. Moreover, miR-34a represses WNT/β-catenin, JAK/STAT3, and PI3K/AKT signaling, all of which have been related to PCa progression [54,86,87]. miR-34a also down-regulates the oncoprotein STMN1 through the CtBP1\miR-34a\STMN1\GDF15 axis and prevents PCa progression in vivo [89].…”
Section: Mir-34mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the identification of many prognostic biomarkers in EC [235,236], none of them are routinely used for diagnostic or prognostic purposes. Recent systematic reviews and meta-analyses revealed the clinical utility for the use of miRNAs as biomarkers in a variety of cancer, including bladder cancer [237], prostate cancer [238], ovarian cancer [239], and breast cancer [240], which makes miRNAs promising candidate for biomarkers in EC (Figure 5). Importantly, dysregulation of miRNAs expression can be also detected in plasma or serum (Figure 5).…”
Section: The Role Of Mirnas In Ec Diagnosis and Managementmentioning
confidence: 99%